Cultural and Socioeconomic Influences on Traditional Medicine Utilization for Treatment of Ear, Nose and Throat (ENT) Conditions - Opoku Agyemang, Cecilia; Opoku, Oscar Agyemang; Serwaa Ennin, Anita; Mabakawo, Gifty; Nyarko Mensah, Olivia; Opoku, Albert (Chakra Brahmanda Lentera Institute, 2025)
Background: Traditional medicine is increasing globally, especially in rural communities of developing countries where it is a preferred treatment option. Various factors, including cultural beliefs, cost, accessibility, and social relationships, influence its utilization. Understanding these factors is essential for developing effective healthcare strategies. This study aims to assess the factors contributing to using traditional medicine in treating Ear, Nose, and Throat (ENT) conditions among ENT patients in Kumasi. Methods: A quantitative descriptive survey design was employed, using a structured questionnaire to collect data from 166 respondents selected through convenience sampling. The data were analyzed using the Statistical Package for Social Sciences (SPSS) to present descriptive statistics. Results: The findings indicate that cultural beliefs significantly influence traditional medicine, with 84.9% of respondents associating it with religious and spiritual underpinnings. Other contributing factors included cost, spirituality, social relationships, and interactions with healthcare workers. Conclusion: Cultural beliefs are crucial in shaping treatment choices for ENT conditions. Public awareness campaigns by the Ministry of Health and local health authorities are recommended to educate communities on the benefits and risks of traditional medicine while promoting evidence-based healthcare practices